(untitled) (Lex Journal : Kajian Hukum dan Keadilan, 2025)
This research aims to understand, explain and analyze the laws used in the process of Consumer Protection of Dropshippers in the Buying and Selling of the Dropshipping System which is reviewed from Law Number 8 of 1999 concerning Consumer Protection. This research method uses the normative legal research method using a statutory approach, a conceptual approach and a comparative approach. The conclusion of the research results obtained is the legal protection for dropshippers that business actors (suppliers) must be responsible for the goods sold by the dropshipper to buyers or consumers who feel aggrieved. Forms of legal protection against dropshipping can be done preventively and repressively. Preventive legal protection efforts are carried out before a violation or legal dispute occurs, with the aim of preventing the violation of rights or abuse of authority. Repressive legal protection is legal protection in dispute resolution through litigation and non-litigation.